2012
DOI: 10.1073/pnas.1112648109
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing humoral responses to a malaria antigen with nanoparticle vaccines that expand T fh cells and promote germinal center induction

Abstract: For subunit vaccines, adjuvants play a key role in shaping immunological memory. Nanoparticle (NP) delivery systems for antigens and/or molecular danger signals are promising adjuvants capable of promoting both cellular and humoral immune responses, but in most cases the mechanisms of action of these materials are poorly understood. Here, we studied the immune response elicited by NPs composed of multilamellar "stapled" lipid vesicles carrying a recombinant Plasmodium vivax circumsporozoite antigen, VMP001, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
283
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(300 citation statements)
references
References 30 publications
14
283
1
2
Order By: Relevance
“…Similarly, other studies have shown improved therapeutic outcomes by either conjugating the adjuvant or the antigen onto or into delivery systems, such as poly(lactideco-glycolide) particles and liposomes, but, to our knowledge, this is the first study to show enhanced co-uptake of both adjuvant and antigen by LN-resident APCs after nanoparticle conjugation (14)(15)(16)(17)(18)(19). Furthermore, it has been shown recently that encapsulating antigens or TLR agonists in nanoparticles enhanced humoral responses compared with immunization with soluble antigen or adjuvant (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies have shown improved therapeutic outcomes by either conjugating the adjuvant or the antigen onto or into delivery systems, such as poly(lactideco-glycolide) particles and liposomes, but, to our knowledge, this is the first study to show enhanced co-uptake of both adjuvant and antigen by LN-resident APCs after nanoparticle conjugation (14)(15)(16)(17)(18)(19). Furthermore, it has been shown recently that encapsulating antigens or TLR agonists in nanoparticles enhanced humoral responses compared with immunization with soluble antigen or adjuvant (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The average ICMV diameter was approximately 375 nm with each harboring on average 160 gp140 trimers for a mean inter-trimer distance of 33 nm [54]. In this instance, Env trimers were displayed greater than tentimes the amount seen on HIV virions while retaining a native orientation on the nanoparticle system designed for efficient delivery of antigens, stable antigen presentation and induction of germinal centers in vivo [54,[56][57][58]. Immunizations with Env-ICMVs in mice-induced Th1/Th2-balanced Env-specific antibodies, IgG 1 and IgG 2c , expanded the breadth of serum antibodies to recognize peptide sequences of two additional Env regions, V2 and membrane-proximal external region (MPER), and increased their titers, compared with soluble protein formulated with a strong oil-inwater emulsion adjuvant [54].…”
Section: Synthetic Nanoparticles For Presentation Of Hiv-1 Antigensmentioning
confidence: 99%
“…Multivalent presentation of PAMPs or antigens by particles mimics repetitive presentation by live pathogens, 63,64 leading to enhanced antigenicity through receptor cross-linking and immune-cell activation. Moon et al 65 demonstrated that particle-based antigen presentation achieved a tenfold reduction in the amount of antigen needed to achieve equivalent antibody responses to that presented by conventional adjuvants. Enhanced diversity in antibody production was also observed with particlebased antigen presentation, potentially due to activation of lower-avidity B cells that would not be achieved with lower antigen densities.…”
Section: Particles As Vaccine-delivery Vehiclesmentioning
confidence: 99%